Alimentação e doenças crônicas não transmissíveis em comunidades quilombolas - VILHENA, Ivana Barbosa de (2023)
This research was designed with the intention of contributing to the debate and quality of food for quilombola peoples in Brazil. Its main objective is to discuss its fundamentals from an interdisciplinary and critical educational approach, which in our understanding should be part of the formation of the lives of subjects aimed at building new perspectives in the development of these situations and problems that are part of the daily life of people in their different food and nutritional singularities. The practice of healthy eating for the people of quilombola communities is of paramount importance for the process of food praxis, which has been configured as a challenge and possibilities to overcome in the face of the difficulties encountered in this diverse environment. In this context, the research was focused on food, as well as being a right of human life, in its various biological and social phases, in which it sought to discover the potential of eating practices that are not restricted to a healthy diet, more on how and which prepositions the effect of eating, which can affect the lives of individuals. To support and deepen the subject proposed here, we worked with books and articles resulting from bibliographic research, specialized magazines and the internet. It revealed that specialized training for these peoples from traditional communities is of paramount importance for a better quality of life. For this, the curricula must create spaces for the articulation of the different sociocultural knowledge produced by social groups, taking into account essential dietary issues to ensure a nutritional quality of life, adequate to the specificities of each subject.